Molecular Identification of Species Diversity Using Pelagic Fish Eggs in Spring and Late Autumn-Winter in the Eastern Beibu Gulf, China - Hou, Gang; Chen, Yanying; Wang, Jinrun; Pan, Chuanhao; Lin, Jianbin; Feng, Bo; Zhang, Hui (Frontiers in Marine Science, 2022)
The Beibu Gulf is ever considered as one of the China’s four major fishing grounds, although the sustantial overexploitation of fisheries has led to the collapse of many fish stocks, and to changes to spawning grounds in recent decades. Classifying fish eggs is an important way to monitor the recruitment process and identify the spawning sites of fish. However, the lack of a basis for morphological identification and difficulties in correctly identifying fish eggs based on morphological characteristics, which limited the scientific studies. In the present study, we identified fish eggs using molecular detection of cytochrome c oxidase subunit I and cytochrome b fragments. Ichthyoplankton surveys were conducted in the spring and late autumn–winter of 2020 in the eastern Beibu Gulf. Among the DNA extracted from the 873 chosen fish eggs, we successfully obtained 541 high-quality cytochrome c oxidase subunit I sequences and 41 high-quality cytochrome b sequences. We successfully identified 212 fish eggs (36.4%) from 32 species; 291 eggs (50.0%) showed ambiguous species delimitation, and 79 eggs (13.6%) could not be identified. Among the identified species, we found 25 species in spring and 25 species in late autumn–winter, out of which 18 species occurred in both seasons. We also obtained high resolution photographs of fish eggs at the species level for further morphological analysis and identification. The present study confirms the efficacy of using molecular methods to identify fish species from eggs and provides valuable information for protecting the spawning ground of economically valuable fish and for managing fishery resources.